Comprehensive State Evaluation of Gearbox based on Relative Health Degree Model - Xianbao Zhao; Zhengnan Xuan; Nianchen Han (Jixie chuandong)
Since the state of operational performance of gearbox proper on the guarantee for smooth of entire device， it is quite significant to monitor and evaluate comprehensively its state of operation. Owing to the limitations of index weight determination in traditional state evaluation method， the entropy model modified G1 is innovatively introduced to scientific and reasonable weight， the concept of relative health degree is proposed， and the grades of health state are classified based on the healthy values to quantitatively describe the running state of gearbox. The analysis of the gearbox fault in certain petrochemical company shows that， this method has better effective in evaluating the gearbox running status， it can provide a theoretical basis for the maintenance based on state.